ON CERTAIN CLASSES OF P-VALENT FUNCTIONS DEFINED BY MULTIPLIER TRANSFORMATION AND DIFFERENTIAL OPERATOR - Tehranchi, A.; Kulkarni, S. R.; Murugusundaramoorthy, G. (Journal of the Indonesian Mathematical Society, 2007)
" PDF File"Â DOI :Â http://dx.doi.org/10.22342/jims.13.1.72.27-38